Community Percpections of the Integration of Islam and Science Hygie Practies in Kampung Tualang - Eliza Putri Ardiah; Z. Zarkasih; Rian Vebrianto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Community life demonstrates that Islamic values and scientific knowledge are closely connected, particularly in hygiene practices. Cleanliness is understood not only as a religious obligation in Islam but also as a scientific requirement for maintaining health. This integration shapes various public perceptions regarding the relationship between Islam and science in everyday life. Therefore, this study aims to explore community perceptions and identify the benefits of integrating Islamic and scientific perspectives on cleanliness. The research employed a mixed-method approach with a case study design. The participants were two women aged 46 and 36 years from Acehnese and Javanese ethnic backgrounds. Data were collected through questionnaires, interviews, and Focus Group Discussions (FGD) conducted directly in the field. Quantitative and qualitative analyses were used to obtain a comprehensive understanding of the phenomenon. The results showed an average score of 4.60, which falls into the very high category. Qualitative findings revealed that participants perceive cleanliness holistically, covering both physical and spiritual dimensions. The integration of Islamic teachings and scientific knowledge has been understood and practiced in daily life, fostering awareness of the importance of cleanliness for faith and health. The study recommends strengthening integrative education and promoting collaboration among religious leaders, healthcare professionals, and government institutions to support sustainable hygiene practices and improve community well-being.